Common Good and Self-Interest as a Problem of Business Ethics - Sójka, Jacek (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
The goal of this article is to argue in favor of such a type of ethical reflection which comes to terms with the unavoidable existence of competition and self-interest as a basic human motivation, which does justice to the market rules of the game, but, at the same time, does not allow itself to embrace the extremities of neoliberal ideology which a priori rejects any state intervention in the markets. Competition in a modern economy which resembles a positive-sum game, can be recognized as constructive element of the market leading to prosperity and economic development. Morality then cannot be construed as rules which favor only restraint, altruism and compassion but rather as a social regulator which creates conditions of fair competition, fair rules of the game. This kind of economic ethics has been elaborated by the followers of the so-called ordoliberalism of Walter Eucken. The ethics of order (Ordnungsethik) or institutional ethics has been focused on the legal and moral order created and safeguarded by a state. The article develops the idea of non-contradictory status of self-interest and common good within the modern economy as a basis for business ethics.